The Effect of Taxes and Tax Refunds on the Economic Activity of the Energy Industry in Peru - Rodriguez, Victor Hugo Puican; Cruz, Liliana del Carmen Suárez Santa; Asalde, Abel Salazar; Suyón, Alejandro Alcántara; Delgado, Freddy Manuel Camacho (International Journal of Energy Economics and Policy, 2024)
Through an empirical analysis of the impact of taxation and tax refunds on the economic activity of the energy industry in Peru, this study seeks to provide an understanding of the economic effects of fiscal policies in a Latin American country with a significant energy sector. Relevant data on taxation and tax refunds in the Peruvian energy sector were collected and the effect of these variables on the main indicator of economic activity in the industry was evaluated. The results suggest that both taxation and tax refunds can significantly impact the economic activity of the energy industry, however, these effects are full when the output of this industry is at medium levels. In addition, the regressive effects of tax taxation can be offset by the positive effects of tax refunds. Overall, this research contributes to understanding the dynamics of fiscal policies in the energy sector of developing economies such as Peru, emphasizing the importance of tailored fiscal measures to promote sustainable energy development and economic growth.